Preschool Teacher’S Knowledge, Skill And Practice Of Hots In Teaching Science Subject - Jaafar, Nurul Izati (2023)
This study investigates the teacher’s knowledge, skill and practice of higher order thinking in teaching preschool children through early science education. A total of 481 questionnaires were completed and obtained from preschool teachers in Peninsular Malaysia. The data was analysed using the SmartPLS Software version 3.0 which used for the Exploratory Factor Analysis and Confirmatory Factor Analysis. The findings indicated that Knowledge of HOTS in the curriculum, Knowledge of HOTS in Pedagogy, Pedagogical skills, Planning/Preparation Skill, Professional Qualification in ECCE/Preschool and KSPK Training/Course have a positive impact on teacher’s practice of HOTS. In addition, the analysis reveals that knowledge of HOTS in curriculum and planning/preparation skills has a positive correlation. Knowledge of HOTS in Curriculum and Pedagogy skills has an insignificant correlation. The moderating effects reveal a positive moderating impact of KSPK Training/Course on the relationship between (Knowledge of HOTS in Curriculum and Knowledge of HOTS in Pedagogy) and teacher’s practice of HOTS. The study provides policy implications to the Ministry of Education (MOE) and stakeholders. MOE should consider directing their emphasis on preschool educational reforms, thus, prioritizing teachers’ development through the maximization of preschool educational resources. Expanding preschool teachers’ training should be consolidated and assigned nationwide to begin yearly.